Fracture of the Femoral Component Caused by Insufficient Crimping after Modern Unicompartmental Knee Arthroplasty - Yoichi Ishibashi; Tasuku Mashiba; Masaki Mori; Tetsuji Yamamoto (Case Reports in Orthopedics)
Fracture of a femoral component after modern unicompartmental knee arthroplasty is very rare. Although this is not the first case on this subject, no study has reported insufficient crimping as the cause of femoral component loosening that led to breakage of a metallic component. A 69-year-old man underwent medial unicompartmental knee arthroplasty for right medial knee osteoarthritis. His early postoperative course was good; however, the 1-year postoperative radiograph showed an apparent radiolucent line around the femoral component, and he occasionally had right knee pain. However, he had been followed up conservatively because he had been doing well even while doing heavy agricultural work. At 8 years after surgery, because breakage of the femoral component was found, revision surgery was performed using bicruciate-retaining total knee arthroplasty. The removed fractured femoral component revealed a thick cement mantle detached from the bone surface. The postoperative course of the patient after the revision surgery was excellent. We suggest that the causes of femoral component breakage include early implant loosening caused by uneven cement crimping of the femoral component to the bone and excessive loading stress as a result of heavy labour.